Human Population Genetics - Relethford, John. (Hoboken : John Wiley & Sons, 2012)
Introductory guide to human population genetics and microevolutionary theory. Providing an introduction to mathematical population genetics, Human Population Genetics gives basic background on the mechanisms of human microevolution. This text combines mathematics, biology, and anthropology and is best suited for advanced undergraduate and graduate study. Thorough and accessible, Human Population Genetics presents concepts and methods of population genetics specific to human population study, utilizing uncomplicated mathematics like high school algebra and basic concepts of probability to explain.
8.4 Estimating Admixture in Human Populations.
Print version record.
Keywords: Human population genetics; Natural history; Science; SOCIAL SCIENCE -- Anthropology -- Physical; Human population genetics; Electronic books